FOSTERING HOTEL EMPLOYEES INNOVATIVENESS THROUGH ORGANIZATIONAL CULTURE AND KNOWLEDGE SHARING - Setiawan, Nyoman; Utami, Hamidah; Afrianty, Tri (TRIKONOMIKA, 2025)
The objective of this study is to examine the influence of both organizational and individual factors, specifically organizational culture (OC) and knowledge sharing behavior (KSB), on innovative work behavior (IWB). The research employed a quantitative method with an explanatory approach to establish causal relationships among the variables through hypothesis testing, utilizing SEM-PLS for data analysis. Data collection was conducted through purposive sampling, involving a total sample size of 91 three-star hotel employees. The analysis indicated that organizational culture positively affects both knowledge sharing behavior and innovative work behavior. Furthermore, knowledge sharing behavior has a direct and indirect significant impact on IWB within the three-star hotel industry employees.